2021
DOI: 10.1017/s0144686x21000647
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequality in long-term care: a comparison of three time periods in the Netherlands

Abstract: As a result of the rapid ageing of societies, meeting the demands for long-term care has become increasingly difficult. In the Netherlands, informal care is recognised as a key element to compensate for cut-backs in formal care provision. Formal, informal and privately paid long-term care services, however, are not used equally across socio-economic status (SES) groups and whether these inequalities have been reduced or exacerbated over time has not been researched. This study investigates to what extent educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It seems obvious that spouses, who spend more time with patients, have the opportunity to provide more informal care. Also, people with lower resources in terms of education and income more often provide informal care because they are less inclined to utilize professional care and often have smaller social networks to assist with caregiving, and as a result, bear the burden of care themselves [ 21 24 ]. Healthcare professionals must be aware of these associations and the impact of these variables, as the desire for a high involvement in care and the inability to mobilize other resources to organize care might eventually contribute to the overloading of family members, which often happens gradually and when it becomes apparent it will become a crisis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems obvious that spouses, who spend more time with patients, have the opportunity to provide more informal care. Also, people with lower resources in terms of education and income more often provide informal care because they are less inclined to utilize professional care and often have smaller social networks to assist with caregiving, and as a result, bear the burden of care themselves [ 21 24 ]. Healthcare professionals must be aware of these associations and the impact of these variables, as the desire for a high involvement in care and the inability to mobilize other resources to organize care might eventually contribute to the overloading of family members, which often happens gradually and when it becomes apparent it will become a crisis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, LTC use is primarily a result of health impairments (Andersen & Newman, 2005), while better physical health (Steptoe et al., 2015) and cognitive functioning (Llewellyn et al., 2008) are both associated with higher PWB. Furthermore, those with higher education report higher wellbeing compared to the lower educated (Navarro‐Carrillo et al., 2020) and also use LTC differently: they use less informal and formal care, but more privately paid care (Abbing et al., 2021). Given that recent cohorts of 75–85‐year‐olds may suffer less from severe health impairments (Verropoulou & Tsimbos, 2017) and are higher educated than their peers in earlier cohorts (Abbing et al., 2021), we control for these variables in our analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, informal care use is stable among lower SES groups; it decreases steeply among higher SES groups. The authors concluded that the findings highlight the importance of education for explaining variation and changes over time in care use (Abbing, Suanet, & van Groenou, 2021).…”
Section: Income and Socioeconomic Statusmentioning
confidence: 93%
“…The results highlighted that healthy life indicators were significantly lower among the no-schooling participants and that older caregivers were associated with weaker enabling variables (Alrashed, 2017). Similarly, in a study of health literacy amongst caregivers of patients with A recent study by Abbing et al (2021) investigates to what extent educational and income inequalities in the use of formal, informal and privately paid care have changed over time in the Netherlands. The authors report that an increase in inequality was only found in the use of informal care.…”
Section: Income and Socioeconomic Statusmentioning
confidence: 96%